Inheritance in the Mandailing Community: Value Changes from a Legal Culture Perspective - Putra Halomoan Hsb; Fatahuddin Aziz Siregar; Suud Sarim Karimullah (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study explores the concept of marbagi dos in relation to the changing inheritance practices of the Mandailing community, viewed through the lens of legal culture. Marbagi dos, which literally means equal in the Mandailing indigenous people, has traditionally had a very important social dimension and equality. The type of research methodology used in this study is qualitative with a descriptive approach. The research data was obtained through interview techniques and participatory observation. In-depth interviews will be carried out with traditional leaders, scholars, and community members who play a direct role in the inheritance process. Using a legal culture approach, this study analyzes how the changes in values in Mandailing society are influenced by Islam which has implications for changes in inheritance practices in Mandailing, as well as how the community balances customary traditions with modern equality demands. The results of the study show that this inheritance transformation is a reflection of the adaptation of the Mandailing people to social changes, while maintaining cultural values within the framework of customary law. The implications of this study suggest that customary law is dynamic and capable of adapting to Islamic law and state law, highlighting the need for synergy between these three legal systems in crafting more inclusive policies.